The regulation of the actin cytoskeleton and cell cycle progression - Heng, Yi Wen (2011)
Cell cycle progression in metazoans proceeds through a series of highly regulated events. In vitro, adherent cell types exhibit substratum adherence and a well spread shape during interphase, which collapse during mitosis to form rounded cells with increased cortical rigidity. After mitosis, there is re-establishment of attachment and cytoskeletal tension. Modulation of such drastic changes in cell shape in synchrony to cell cycle progression suggests tight signalling regulation between cytoskeleton dynamics and cell cycle progression. We aim to study the regulatory links between the actin cytoskeleton, its regulators and effectors on the cell cycle progression. We found that perturbation of actin using various drugs were able to alter the timings of progression into various cell cycle stages. In addition, we observed that the RhoA signalling pathway can control metaphase astral microtubules formation through its effector ROCK, LIMK2 and its novel substrate tubulin polymerising promoting protein (TPPP), and thus affect spindle orientation. Finally, we suggest that LIMK1 and LIMK2 can play differential role during mitosis; LIMK1 modulating centrosomes integrity and LIMK2 regulating astral microtubules formation.